Joseph Hickey letter to Oscar Allert regarding Peregrine Falcon sightings, October 3, 1939 - Hickey, Joseph J. (Joseph James), 1907-1993et al (1939)
Letter from Joseph Hickey to Oscar Allert dated October 3, 1939. Hickey asks for more information on Peregrine Falcons in eastern Iowa after reading Allert's article "Notes on Certain Raptores in Allamakee, Clayton and Dubuque Counties, Iowa," published in Iowa Bird Life, vol. 9, no. 3. Epson - sheet feed/flatbed